Managing talents through succession planning in the Malaysian public sector / Hamizam Abdulla Zabidi...[et al.] - Abdulla Zabidi, Hamizam; Mansor, Joesfina Syawati; Ahmad, Jasmine (2010)
Succession planning is not a new concept but recently redefined and reemphasized due to the importance of ensuring there is talent continuity in an organization. This is especially when there is so much buzz on the notion that retaining and managing the right talents is one of the main survival elements of an organization in the competitive world. In implementing such concept, the main issue of interest is identifying the suitable dimensions needed to build a sophisticated and solid succession planning model. This concept paper is aimed to explain the various literatures of succession planning in managing talents. From the various literatures, the paper attempts to identify the key elements to conceptually build a succession planning model which will fit within the Malaysian public sector scenario. Primarily, the paper is based on various literatures and reports available about the concept. Specifically, the literatures and reports referred are those which focus on the dimensions of the various approaches. In addition, the identification of the key dimensions for Malaysian public sector is done through comparing specific perspectives of different approaches suggested by various literatures reviewed. The finding would give some insights on succession planning as a major tool in managing talents in Malaysian public sector’s scenario.